POPULATION DENSITY OF LEAF-EATING MONKEYS AND DOMINANT VEGETATION AT THE IPUKAN, GUNUNG CIREMAI NATIONAL PARK, INDONESIA - Toto Supartono; Robi Robi; Nurdin Nurdin (Faculty of Forestry and Environment, Universitas Kuningan, 2018)
The purpose of this study was to analyze the population density of leaf-eating monkeys (javan langur and girzzled leaf monkey) and vegetation dominating their habitat. The research has been done in the Ipukan of Gunung Ciremai National Park and used line transect method for population data collection and sample plot for data collection of vegetation. The results showed that the population density was 0.49 animals/ha for javan langur and 0.24 animals/ha for grizzled leaf monkey and the mean of group size were 7.42 and 8 animals, respectively. Vegetation was dominated by Pinus merkusii, followed by Ficus fistulosa, Macaranga rhicinoides, and Ficus ribes indicating that monkey habitat was a modified ecosystem and secondary forest. Keywords: conservation, grizzled leaf monkey, javan langur, Presbytis comata, Trachypithecus auratus.